The concept of products and services integration – analysis of scientific publications - Kozłowska, Justyna (Business, Management and Economics Engineering, 2016)
Currently, global economy tends to turn into functional economy what triggered the birth of new terms and research fields such as integration of products and services (in literature termed: Product-Service Systems). Though the subject is often discussed in scientific and academic publications, there are still many aspects of developing and delivering integrated solutions to customers insufficiently explored or even neglected. The paper presents the concept of an integrated product-service solution. The analysis of publications in terms of research topics connected with Product-Service Systems was carried out and the achieved results were discussed.